Symptoms of Nitrogen and Iron Deficiency in Luffa - Qiansheng Li; Marina Gluck; Yanlin Wang; Wendy Mussoline; Qingren Wang; Yuncong Li; Guodong Liu (EDIS)
Luffa (Luffa aegyptiaca, synonym Luffa cylindrica) is a tropical and subtropical climbing plant belonging to the cucumber family (Cucurbitaceae), natively cultivated in South and Southeast Asia. There are two main species of luffa grown in Florida: smooth luffa (Luffa aegyptiaca Mill.), primarily grown in small gardens and angled luffa (Luffa acutangula (L.) Roxb.), basically grown for commercial production (https://edis.ifas.ufl.edu/publication/HS1285). It is commonly called sponge gourd, Egyptian cucumber, or Vietnamese luffa. Young fruits are edible and rich with nutritional and medicinal value (Partap et al. 2012; Azeez, Bello, and Adedeji et al. 2013). The mature fruit has strong fibrous insides, which can be used as natural porous fiber (Siqueira, Bras, and Dufresne 2010; Sivakandhan et al. 2020) for dishwashing or shower scrubbing. This publication is written for growers, state and county Extension faculty, and students interested in crop production.